Price authority and information sharing with competing principals - Enrique Andreu; Damien J. Neven; Salvatore Piccolo (Graduate Institute of International and Development Studies, 2022)
We characterize the degree of price discretion that competing principals award their agents in a framework where agents are informed about demand and seek to pass on their unveriÖable distribution costs to consumers at the principalsí expense. Principals learn demand probabilistically and may exchange this information on a reciprocal basis. While equilibria with full price delegation never exist, partial delegation equilibria exist with and without information sharing and feature binding price caps (list prices) that prevent agents from passing on their distribution costs to consumers. Yet, these equilibria are more likely to occur with than without information sharing. Moreover, while principals exchange information when products are suffi ciently dierentiated and downstream distribution costs are not too low, expected prices are unambiguously lower with than without information sharing. These results have potential implications for recent and ongoing antitrust investigations and damage claims in prominent sectors both in the US and the EU.
Keywords: L42; L50; L81; 330; Competing Principals; Delegates Sales; Discretion; Information Sharing; List Prices